(untitled) (Research, Society and Development, 2022)
Antimicrobials for domestic, hospital, veterinary and agricultural use have aroused increasing concern, due to the presence of these residues in the aquatic environment, even at very low concentrations, they can potentially interfere with the balance of aquatic biota, affecting populations of primary producers. Of the microorganisms, microalgae are considered one of the most sensitive, in addition to being more susceptible, as they are distributed throughout the aquatic environment. The present study was to evaluate the effects of antibiotic substances on the growth of the microalgae Chlorella vulgaris. The results indicate that the antibiotics, Amoxicillin, Ampicillin and Cephalexin monohydrate, belonging to the beta-lactam group, have a higher cell density compared to the control treatment, inhibiting the growth of C. vulgaris. The study suggests carrying out monitoring in the environmental matrices, mainly in the northern region, as it presents a low percentage in the conventional treatment of sanitary sewage, thus avoiding risks to the aquatic biota and human health.